2019
DOI: 10.1021/acs.langmuir.8b04256
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Formulation Method, Lipid Composition, and PEGylation on Vesicle Lamellarity: A Small-Angle Neutron Scattering Study

Abstract: Liposomes are well-established systems for drug delivery and biosensing applications. The design of a liposomal carrier requires careful choice of lipid composition and formulation method. These determine many vesicle properties including lamellarity, which can have a strong effect on both encapsulation efficiency and the efflux rate of encapsulated active compounds. Despite this, a comprehensive study on how the lipid composition and formulation method affect vesicle lamellarity is still lacking. Here, we com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 39 publications
10
75
0
Order By: Relevance
“…Similarly, any factor that lowers the bilayer adhesion energy, such as increasing interlamellar repulsion with charged lipids (12), also favors separation of layers and should therefore increase the fraction of unilamellar vesicles after extrusion. It is likely that bending energy also contributes to an increased probability of unilamellar vesicles upon hydration (i.e., prior to extrusion), as recently proposed (13). Indeed, we found that the lipid with the largest bending modulus (ESM) had the greatest fraction of unilamellar vesicles both before and after extrusion (Table S2).…”
Section: Statement Of Significancesupporting
confidence: 80%
See 1 more Smart Citation
“…Similarly, any factor that lowers the bilayer adhesion energy, such as increasing interlamellar repulsion with charged lipids (12), also favors separation of layers and should therefore increase the fraction of unilamellar vesicles after extrusion. It is likely that bending energy also contributes to an increased probability of unilamellar vesicles upon hydration (i.e., prior to extrusion), as recently proposed (13). Indeed, we found that the lipid with the largest bending modulus (ESM) had the greatest fraction of unilamellar vesicles both before and after extrusion (Table S2).…”
Section: Statement Of Significancesupporting
confidence: 80%
“…The presence of multilamellar structures in extruded vesicles has been sporadically reported in the literature, often evidenced by their clear experimental signature in scattering studies (9,13,21). Some factors that can potentially influence multilamellarity are the number of freeze-thaw cycles (22), membrane lipid composition (9), and modification of lipid headgroups, for example by PEG polymers (13,(22)(23)(24).…”
Section: Statement Of Significancementioning
confidence: 93%
“…Earlier investigations of liposome production by millifluidics have predominately focused on a limited number of model lipid formulations. Since liposomes’ properties are very often dependent upon their lipid compositions [ 61 ], a further verification of the reactor’s performance was carried out by producing liposomes of different formulations comprising PC, DPPC, Chol, ODA, and PEG-40. PC (soybean) is one of the most common lipids used in liposomal formulations due to its abundance in animals and plants, and DPPC is often used in thermosensitive formulations and is often a key constituent in membrane models [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…In order to t the SANS data for PEGMA x -b-BuMA y -b-DEGMA z above the T degel , we used a BroadPeak model, which provided the best-t position of the Bragg peak. 60 This model is a combination of a Lorentzian-peak function and a power law decay and could suggest the presence of a bicontinuous structure 61 above the T degel . As is seen in Fig.…”
Section: Rheological Properties and Self-assembly Behaviourmentioning
confidence: 97%